Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68411
|View full text |Cite
|
Sign up to set email alerts
|

Study of Convective Flow Effects in Endwall Casing Treatments in Transonic Compressor Rotors

Abstract: The unsteady convective flow effects in a transonic compressor rotor with a circumferential-groove casing treatment are investigated in this paper. Experimental results show that the circumferential-groove casing treatment increases the compressor stall margin by almost 50% for the current transonic compressor rotor. Steady flow simulation of the current casing treatment, however, yields only a 15% gain in stall margin. The flow field at near-stall operation is highly unsteady due to several self-induced flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The design of flow control devices is a key point to improve the performance of compressors and better manage surge margin [33]. A lot of solutions have been proposed in the literature such as active flow control [34,35] and casing treatments [36][37][38], but the flow control mechanisms are not yet completely understood [39,40]. The prediction of a control devices effectiveness is a challenge in itself due to the complexity of the flow that develops in a compressor equipped with a control solution (figure 2).…”
Section: Review Of Some Challengesmentioning
confidence: 99%
“…The design of flow control devices is a key point to improve the performance of compressors and better manage surge margin [33]. A lot of solutions have been proposed in the literature such as active flow control [34,35] and casing treatments [36][37][38], but the flow control mechanisms are not yet completely understood [39,40]. The prediction of a control devices effectiveness is a challenge in itself due to the complexity of the flow that develops in a compressor equipped with a control solution (figure 2).…”
Section: Review Of Some Challengesmentioning
confidence: 99%
“…Even for the same compressor, stall margin extensions are usually irregular at different rotating speed. The modern powerful computers make it possible to utilize numerical simulations, especially with the advanced high-fidelity computational models, to explore in details the flow structures and the stalling mechanism with and without casing treatments [6]. However, due to the complexity of the stall phenomena, the mechanism of the stall margin improvement by CT is still not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the detailed investigations reported on circumferential groove casing treatment are based on steady-state numerical simulations and emphasize the important role of the grooves on the strength and position of the leakage vortex. [5][6][7][8][9] However, Hah et al 10 showed both experimentally and numerically that the flow field near the tip of a transonic compressor rotor with circumferential grooves can be ''highly unsteady'', implying that steady calculations are inadequate.…”
Section: Introductionmentioning
confidence: 99%